Impact of residual contamination on inclusive and direct photon flow. (13th January 2017) - Bock, F; Loizides, C; Peitzmann, T; Sas, M
Abstract: Direct photon flow is measured by subtracting the contribution of decay photon flow from the measured inclusive photon flow via the double ratio R γ, which defines the excess of direct over decay photons. The inclusive photon sample is affected by a modest contamination arising from different background sources, which can not always be fully corrected for in measurements. However, due to the sensitivity of the direct photon measurement even a residual contamination may significantly bias the extracted direct photon flow. In particular, for measurements using photon conversions, which are very powerful at low transverse momentum, these effects can be substantial. Assuming three different types of correlated background contributions we demonstrate using the Therminator2 event generator that the impact of the contamination on the magnitude of direct photon flow can be on the level of 50%, even if the purity of the inclusive photon sample is about 97%. Future measurements should attempt to account for the contamination by measuring the background contributions and subtracting them from the inclusive photon flow.